Tizenkét perc Alekszej Fjodorovics Merekalov életéből - Kolontári, Attila (Közép-Európai Közlemények, 2020)
In the second part of the 1930s, the Central and Eastern European region with its little, vulnerable countries often conflicting with each other turned into a buffer zone, an object of bargain between Nazi Germany and Stalin’s Soviet Union. The German–Soviet Non-Aggression Agreement and its Secret Protocol, more commonly known after the signatory parties as Molotov–Ribbentrop Pact, was a result of long negotiations involving many diplomats, experts etc. Among them A. F. Merekalov belongs to the group of less known personalities. He was a Soviet ambassador to Berlin in 1938–1939. Although mainly the year of 1939 was an intensive period in Soviet–German contacts, Ambassador Merekalov played only an episode role in these processes. In spite of this, there were some moments when he got in the focus of attention in diplomatic circles and in the world press. The most famous event of Merekalov’s short diplomatic career was the New Year Reception in the building of the Imperial Chancellery given by Hitler for the members of diplomatic corps. To the greatest surprise of those present, Hitler – while diplomats were being introduced to him – entered into a friendly conversation with the Soviet ambassador which took longer than it was prescribed by protocol. Many consider that it was a signal to Stalin expressing the Führer’s readiness to reach an agreement with Moscow. From archival documents it turned out that it was not an improvisation, Hitler had consciously prepared for this conversation, a report about Merekalov’s characteristics was later found in the archives of one of his adjutants. The present paper examines the circumstances of this conversation, its place on the path towards the Pact and Merekalov’s role in these processes.